Paramagnetic effect of the magnetic field on superconductors with charge-density waves - Ekino, T.; Gabovich, A.M.; Voitenko, A.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
The limiting field Hp for spin-singlet superconductors with charge-density waves (CDWs), which paramagnetically destroys the ordered phase, possessing coexisting superconducting andCDW order parameters, is calculated self-consistently. It is shown that Hp always exceeds the Pauli limits both for pure superconducting and pure CDW phases. Relevant experimental data for inorganic and organic superconductors with high upper critical magnetic fields are analyzed and are shown to be in qualitative agreement with the proposed theory.